ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA: STUDI KASUS DI BENGKEL KENDARAAN RINGAN DI SMK KARSA MULYA PALANGKA RAYA - Maulana, Fazar; Debora, Debora; Samudra, Agung (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
This study aims to analyze whether the use and feasibility of facilities and PPE applied in the light vehicle practical workshop in implementing K3 implementation is good and correct and to analyze whether the Standard Operating Procedure for K3 implementation carried out in the workshop of SMK Karsa Mulya Palangka Raya is good and appropriate. The type of research used is qualitative with a case study approach method. Data collection techniques using observation, interview methods, and documentation methods. The data analysis technique used in this research is qualitative data analysis technique. The results of this study indicate that the use of PPE and the feasibility of facilities in the light vehicle practical workshop at SMK Karsa Mulya in implementing K3 show that the facilities and completeness of PPE used are still incomplete. The application of the K3 SOP is still not implemented according to K3 guidelines and the legal basis regulations are still unclear